Implementasi Kebijakan Penyaluran Beras Rakyat Miskin Di Desa Poopoh Kecamatan Tombariri Kabupaten Minahasa - Mangende, Haryati Duplin; Rumapea, Patar; Palar, Novie Anders (Sam Ratulangi University, 2016)
Abstract :Raskin is a government program that purpose to reduce the burden of spending Objective HouseholdsOwn Benefit (RTS-PM) through a partial fulfillment of basic needs in the form of rice. However, implementation ofthe policy has not worked as expected due to several factors between like low quality of rice delivered, in factobjective’s receiver of subsidized rice is not only the poor but the society who belong to afford. The purpose of thisstudy was to determine how the distribution policy implementation Raskin in the village Poopoh TombaririSubdistrict Minahasa district. To realize these purpose, Conducting research using descriptive qualitativeapproach. The data resources consist of primary data result from observation and interviews, and secondary dataresult from the management of documents, archives, records, and regulations related to issues in research. Theresults showed that the rice’s distribution policy implementation of poor society in the Poopoh Village TombaririSubdistrict Minahasa District has not accomplished appropriate with the purpose and objectives becauseimplementing no transparency in the distribution of rice’s raskin. Raskin distribution policy implementation refer toindicator of 6 success exact is not achieve.Keywords: Implementation Policy Rice Distribution for Poor Society